2019
DOI: 10.1038/s41598-019-55291-8
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Hyperandrogenemia and Obesogenic Western-style Diet on Transcription and DNA Methylation in Visceral Adipose Tissue of Nonhuman Primates

Abstract: Polycystic ovary syndrome (PCOS) is a major reproductive disorder that is responsible for 80% of anovulatory infertility and that is associated with hyperandrogenemia, increased risk of obesity, and white adipose tissue (WAT) dysfunction. We have previously demonstrated that the combination of chronic testosterone (T) treatment and an obesogenic Western-style diet (WSD) exerts synergistic functional effects on WAT, leading to increased lipid accumulation in visceral adipocytes by an unknown mechanism. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 87 publications
(133 reference statements)
3
13
0
Order By: Relevance
“…To address the impact of maternal obesity on FBM development and hematopoiesis, we studied two experimental groups of female rhesus macaques, including those that consumed either a low-fat control diet or those consuming a calorie-rich high-fat WSD for 3 years starting at 2.5 years of age (near menarche) ( Figure 1A ). Animals consuming the WSD were consistently heavier and exhibited significantly greater percentage total body fat than control animals, as previously reported (Carbone et al, 2019; Varlamov et al, 2017) ( Figures 1B and C ). At 5.5 years of age, animals underwent timed-mated breeding (Bishop et al, 2021).…”
Section: Resultssupporting
confidence: 87%
“…To address the impact of maternal obesity on FBM development and hematopoiesis, we studied two experimental groups of female rhesus macaques, including those that consumed either a low-fat control diet or those consuming a calorie-rich high-fat WSD for 3 years starting at 2.5 years of age (near menarche) ( Figure 1A ). Animals consuming the WSD were consistently heavier and exhibited significantly greater percentage total body fat than control animals, as previously reported (Carbone et al, 2019; Varlamov et al, 2017) ( Figures 1B and C ). At 5.5 years of age, animals underwent timed-mated breeding (Bishop et al, 2021).…”
Section: Resultssupporting
confidence: 87%
“…In summary, the present study advances our understanding of the functional and transcriptional response in SC-WAT associated with dynamic changes in fat mass in response to diet-induced obesity and weight loss and expands our previous studies in NHPs [17,18,20,[64][65][66]. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 64%
“…Consistent with this hypothesis, we recently conducted the whole-genome gene expression and epigenetic analysis in visceral WAT of female rhesus macaques exposed to a WSD and excess androgens in combination or individually. This study demonstrated that testosterone could modulate the effects of WSD on transcription of lipid metabolism genes and DNA methylation in females WAT [64].…”
Section: The Effects Of Wsd and Cr On De Novo Lipogenesis Pathwaymentioning
confidence: 67%
“…Therefore. prenatally androgenized (PNA) models ( 39 ) or testosterone-treated models ( 20 ) were used as PCOS-like models for hyperandrogenism basis, which would highly increase the expression of AR ( 40 ). In our findings, AR was identified as the common TF of STON1 and FSHR and positively correlated with their expression in ovary tissues.…”
Section: Discussionmentioning
confidence: 99%